Analisis Pengaruh Tata Guna Lahan Terhadap Perubahan Karakteristik Hidrograf Banjir di Sub DAS Sungai Negara Kota Amuntai - Awaludin, Muhammad Syahli Roby; Amal, Nilna (Universitas Trunojoyo Madura, 2025)
Seasonal flooding in Amuntai City, located in the downstream area of the Negara Sub-watershed, has become increasingly frequent, with land-use change identified early as one of the main contributing factors. This study aims to model flood hydrographs under the land-use conditions of 2006, 2015, and 2022, and to analyze the impact of land-use conversion on the characteristics of flood hydrographs. The modeling was carried out using HEC-HMS with rainfall inputs distributed hourly using the Mononobe Method and the Alternating Block Method (ABM). Hydrological parameters, including Curve Number (CN), initial abstraction, and imperviousness, were obtained through spatial analysis using QGIS. The results indicate that land-use change has a direct influence on the hydrological response of the sub-watershed, as reflected by an increase in peak discharge from 115.9 m³/s in 2006 to 120.8 m³/s in 2015 (a 4.23% rise), and a more substantial increase to 136.4 m³/s in 2022 (a 12.91% rise from 2015, or 17.7% from 2006). In addition, acceleration of the time to peak (Tp) and shortening of the time base (Tb) were observed, indicating increased surface runoff due to reduced soil infiltration capacity as built-up areas expanded. These findings affirm that land-use conversion significantly contributes to heightened flood vulnerability in downstream areas. This study also highlights the need for more complete observational hydrograph data to enhance model accuracy in future research, and encourages the use of alternative modeling to obtain more comprehensive insights in support of sustainable watershed management strategies.